Rapidly diverging evolution of an atypical alkaline phosphatase (PhoAaty) in marine phytoplankton: insights from dinoflagellate alkaline phosphatases - Lin, Xin; Wang, Lu; Shi, Xinguo; Lin, Senjie (Frontiers in Microbiology, 2015)
Alkaline phosphatase (AP) is a key enzyme that enables marine phytoplankton to scavenge phosphorus (P) from dissolved organic phosphorus (DOP) when inorganic phosphate is scarce in the ocean. Yet how the AP gene has evolved in phytoplankton, particularly dinoflagellates, is poorly understood. We sequenced full-length AP genes and corresponding complementary DNA (cDNA) from 15 strains (10 species), representing 4 classes of the core dinoflagellate lineage, Gymnodiniales, Prorocentrales, Suessiales and Gonyaulacales. Dinoflagellate AP gene sequences exhibited high variability, containing variable introns, pseudogenes, single nucleotide polymorphisms and consequent variations in amino acid sequence, indicative of gene duplication events and consistent with the “birth-and-death” model of gene evolution. Further sequence comparison showed that dinoflagellate APs likely belong to an atypical type AP (PhoAaty), which shares conserved motifs with counterparts in marine bacteria, cyanobacteria, green algae, haptophytes and stramenopiles. Phylogenetic analysis suggested that PhoAaty probably originated from an ancestral gene in bacteria and evolved divergently in marine phytoplankton. Because variations in AP amino acid sequences may lead to differential subcellular localization and potentially different metal ion requirements, the multiple types of APs in algae may have resulted from selection for diversifying strategies to utilize DOP in the P variable marine environment.